Comparison of diagnostic effectiveness of X-ray computed tomography, magnetic resonance imaging and diffusion-weighted magnetic resonance imaging in the differentiation of residual tumors and posttherapeutic masses in patients with lymphoma after treatment - S. A. Khoruzhik; E. A. Zhavrid; N. V. Sachivko (Онкогематология, 2016)
We conducted prospective study of the effectiveness of X-ray computed tomography (CT), magnetic resonance imaging (MRI) and MRI with diffusion-weighted imaging (MRI-DWI) with apparent diffusion coefficient (ADC) maps calculation for the differentiation of residual tumors and posttherapeutic masses in 40 adult patients with lymphoma. Whole body CT and MRI-DWI were performed before and after treatment.The effectiveness of lesions size criterion for CT and MRI, visual and quantitative criteria for MRI-DWI were investigated. Residual lesions signal intensity on DWI images and ADC maps was compared with paraspinal muscles signal intensity. The accuracy of the overall tumor response estimation was 38 % for CT, 48 % for MRI, 68 % for MRI-DWI with visual assessment of DWI images, 93 % for MRI–DWI with visual assessment of ADC maps. CT density of the lymph node lesions before treatment and residual masses after treatment did not differ significantly – 40.4 ± 9.4 and 37.2 ± 10.5 Hounsfield units respectively (p = 0.08), whereas ADC (×10–3 mm2/s) increased significantly from 1.04 ± 0.40 to 2.01 ± 0.82 (p < 0.0001). ADC of postherapeutic masses was significantly higher than that of residual tumors – 2.32±0.62 and 1.04 ± 0.66 respectively (p < 0.0005). MRI-DWI with visual assessment of ADC maps is the most effective method for differentiation of residual tumors and posttherapeutic masses in patients with lymphoma after treatment. Usefulness of quantitative analysis of ADC values requires further investigation.